Energy utilization by Somali lambs fed napiergrass “ad libitum” and an energy supplement at incremental levels - Barros, Nelson Nogueira; Kawas, Jorge; Johnson, William Lawrence; Shelton, Joseph Maurice (Pesquisa Agropecuaria Brasileira, 2014)
A twelve-week study was conducted to determine the influence of the level of energy supplementation on forage and total diet dry matter intake and energy utilization by growing Somali lambs. Thirty-six male lambs were randomly blocked among four energy levels. To all lambs were offered a daily protein supplement at 0.5% of the body weight and an energy supplement ranging from 0.4 to 1.6% of the body weight. Napiergrass green chop was offered ad libitum. Lambs were harnessed for total collection of feces during the last 7 days of the study. Forage and total dry matter intake decreased (P < 0.05) with an increase in energy supplementation. Dry matter digestibility, digestible energy intake, body weight and feed efficiency increased (P < 0.05) with an increase in the level of energy in the diet. From the regression of metabolizable energy intake (Kcal/kg°-75/day) on body weight gain (g/day) the estimated daily ME requirements for maintenance was 73 Kcal/kg°- 75 and for live weight gain was 0.90 Kcal ME/g gain/kg° -75.